The efficacy of neuromuscular training, with minimal or no equipment, on performance of youth athletes: A systematic review with meta-analysis - Muller, M. R.; Lemes, Í. R.; Silva, M. S. C.; Silva, N. S.; Hernández, A. G.; Pinto, R. Z. (Physical Therapy in Sport, 2023)
Objectives To investigate the effects of neuromuscular training, with minimal or no equipment, on physical performance of youth athletes.